2019
DOI: 10.3390/ijms20112732
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 Feedback Enhances BMPR1B Transcription in Ovine Granulosa Cells

Abstract: BMPR1B is a type 1B receptor of the canonical bone morphogenetic protein (BMP)/Sma- and mad-related protein (Smad) signaling pathway and is well known as the first major gene associated with sheep prolificacy. However, little is known about the transcriptional regulation of the ovine BMPR1B gene. In this study, we identified the ovine BMPR1B gene promoter and demonstrated that its transcription was regulated by Smad4. In sheep ovarian follicles, three transcriptional variants of BMPR1B gene with distinct trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…One of the highlights of this study is that we showed that SMAD4, the only Co-SMAD, has feedback activities to induce the expression of upstream receptors in GCs with a basal level of TGF-β ligands. As known, the ligands of TGF-β family signaling pathways, such as BMPs and TGF-βs, are secreted from GCs and further influence the activities of downstream signaling through both autocrine and paracrine methods [ 32 , 33 ]. Until now, few studies have reported the feedback activities of SMAD4 with exogenous ligands addition.…”
Section: Discussionmentioning
confidence: 99%
“…One of the highlights of this study is that we showed that SMAD4, the only Co-SMAD, has feedback activities to induce the expression of upstream receptors in GCs with a basal level of TGF-β ligands. As known, the ligands of TGF-β family signaling pathways, such as BMPs and TGF-βs, are secreted from GCs and further influence the activities of downstream signaling through both autocrine and paracrine methods [ 32 , 33 ]. Until now, few studies have reported the feedback activities of SMAD4 with exogenous ligands addition.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor 2 has been studied to play vital roles in the ovary during egg-laying stages and may be closely related to laying performance in ducks and may regulate key genes in granulosa cells essential for follicle maturation and ovulation ( Wu et al., 2014 ; Khristi et al., 2018 ). Bone morphogenetic protein receptor beta is a member of the TGF-β superfamily which is firstly expressed in primordial follicles on the oocyte and granulosa cells of primary follicles throughout folliculogenesis ( Regan et al., 2018a ; Abdurahman et al., 2019 ; Zhang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMPR1B (FecB) is one of the major fecundity genes in female reproduction and plays a major role in the development of follicles and the proliferation of ovarian granulosa cells in sheep (Shimasaki et al, 1999;Chu et al, 2007;Yao et al, 2019;Tao et al, 2019;Abdurahman et al, 2019). Previous reports have found that BMPR1B belongs to the type I receptors of BMPs (Aquino et al, 2017), which figure prominently in the proliferation of primordial germ cells (PGCs) (Nermin et al, 2018;Yi et al, 2001) and in the production and secretion of reproductive hormone (Richards and Pangas, 2010;Isaacs et al, 1995) by binding specifically to different types of ligands (Ikeda et al, 2016).…”
Section: Effect Of Bmpr1b Gene Expression On Mammalian Reproductionmentioning
confidence: 99%